If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -8) = 9(x + -2) Reorder the terms: 8(-8 + x) = 9(x + -2) (-8 * 8 + x * 8) = 9(x + -2) (-64 + 8x) = 9(x + -2) Reorder the terms: -64 + 8x = 9(-2 + x) -64 + 8x = (-2 * 9 + x * 9) -64 + 8x = (-18 + 9x) Solving -64 + 8x = -18 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -64 + 8x + -9x = -18 + 9x + -9x Combine like terms: 8x + -9x = -1x -64 + -1x = -18 + 9x + -9x Combine like terms: 9x + -9x = 0 -64 + -1x = -18 + 0 -64 + -1x = -18 Add '64' to each side of the equation. -64 + 64 + -1x = -18 + 64 Combine like terms: -64 + 64 = 0 0 + -1x = -18 + 64 -1x = -18 + 64 Combine like terms: -18 + 64 = 46 -1x = 46 Divide each side by '-1'. x = -46 Simplifying x = -46
| 4x^2+9x=3 | | 3(4x-5)-(2x+3)=2(x-4) | | -2(-2)-3(3)+3(-4)= | | -48--22= | | -4(4)-3(-8)= | | -0.9=4b-4.1 | | 7x^2-4x+3=0 | | -7(m+5)= | | 12-8x=35-15x | | 6x+7=-133-8x | | x(-2x-13)=-2 | | 4n-7n= | | -6t+t-2t= | | h=-16h^2+96h | | -5t+t-7t= | | (X+13)+(2X+23)=90 | | -5x-12x=119 | | (4+z)(4z-1)=0 | | -7x-11x=72 | | 77189/= | | 3v(v+4)(v+5)=0 | | 0.80x+.05(4-x)=.10(-73) | | 7x-11x=72 | | 4(6+4)+2= | | 2x^2-23+63=0 | | (9-z)(3z+2)=0 | | 66x^2=0 | | 2(v+9)(-v+3)=0 | | 9a-12a+6=-1 | | (3z+1)(4+z)=0 | | 3x^2-4x-8=-4 | | (u+5)(u-6)=0 |